Functional significance and welfare implications of chewing in dogs (Canis familiaris) - Quinn, Rimini; Masters, Sophie; Starling, Melissa; White, Peter John; Mills, Kathryn; Raubenheimer, David; McGreevy, Paul (Frontiers in Veterinary Science, 2025)
Dogs chew on both nutritive and non-nutritive items as part of their food acquisition, ingestive behaviour, self-care, and social interactions. Various definitions distinguish chewing from related oral activities, such as gnawing, masticating, and biting. Surprisingly, despite chewing being a ubiquitous behaviour in dogs, its relevance to a dog’s comfort, health, and purpose remains unclear. Additionally, the risk of dental fractures or other injuries may lead veterinarians to advise against feeding bones to dogs. This article explores the literature on chewing in dogs through the ethological framework of “Tinbergen’s Four Questions” and the Five Domains framework for animal welfare assessment. Evidence is gathered from wild and domestic canids and from human and animal models where shared physiological or biological processes provide insight. Chewing appears to promote biological fitness, providing benefits such as dental and oral hygiene, digestive health, bone strength, psychological health, and stress management. Furthermore, this article discusses the evolutionary importance of chewing, the mechanisms underlying bite force, chew rate and morphology, and the development of chewing throughout a dog’s life, from primary teeth eruption to senescence. Application of the Five Domains framework for animal welfare helps assess the impact of chewing, or lack thereof, on a dog’s welfare. A dog’s preference for chew items is primarily driven by odour, taste, and mouthfeel. Macronutrient proportions may also play a role in food preferences, which, in turn, can affect the selection of chewable items. A lack of preferred chew items may result in redirected chewing toward less appropriate items, such as non-food chews that could be harmful to dentition or the gastrointestinal tract (GIT). Chewing on such inappropriate items may also lead to the adoption of alternative oral behaviours or reduced their contentment by impeding telos. Overall, chewing positively impacts a dog’s physical and psychological health, contributing to its welfare and appearing essential as a regular part of a dog’s daily life. However, the significant benefits of chewing must be carefully weighed against potential risks.